Comparative transcriptome analysis during developmental stages of direct somatic embryogenesis in Tilia amurensis Rupr - Hye-In Kang; Chae-Bin Lee; Soon-Ho Kwon; Ji-Min Park; Kyu-Suk Kang; Donghwan Shim (Scientific Reports, 2021)
Abstract Tilia species are valuable woody species due to their beautiful shape and role as honey trees. Somatic embryogenesis can be an alternative method for mass propagation of T. amurensis. However, the molecular mechanisms of T. amurensis somatic embryogenesis are yet to be known. Here, we conducted comparative transcriptional analysis during somatic embryogenesis of T. amurensis. RNA-Seq identified 1505 differentially expressed genes, including developmental regulatory genes. Auxin related genes such as YUC, AUX/IAA and ARF and signal transduction pathway related genes including LEA and SERK were differentially regulated during somatic embryogenesis. Also, B3 domain family (LEC2, FUS3), VAL and PKL, the regulatory transcription factors, were differentially expressed by somatic embryo developmental stages. Our results could provide plausible pathway of signaling somatic embryogenesis of T. amurensis, and serve an important resource for further studies in direct somatic embryogenesis in woody plants.